2017
DOI: 10.1007/978-3-319-63245-2_11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hyperoxia on the Developing Airway and Pulmonary Vasculature

Abstract: Although it is necessary and part of standard practice, supplemental oxygen (40-90% O) or hyperoxia is a significant contributing factor to development of bronchopulmonary dysplasia, persistent pulmonary hypertension, recurrent wheezing, and asthma in preterm infants. This chapter discusses hyperoxia and the role of redox signaling in the context of neonatal lung growth and disease. Here, we discuss how hyperoxia promotes dysfunction in the airway and the known redox-mediated mechanisms that are important for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 138 publications
0
7
0
Order By: Relevance
“…Mechanisms in the context of inflammation (Hartman et al, 2012), hypercontractility (Faksh et al, 2016), and fibrosis (Vogel et al, 2017) have been explored to some extent. In this regard, there is increasing recognition that O 2 effects in specific cell types and the types of changes are dependent on extent of exposure structure/function, where with higher levels of O 2 promote bronchopulmonary dysplasia (Wang et al, 2014;Pabelick et al, 2017), but even moderate hyperoxia can contribute to bronchial changes. For example, at a cellular level, we previously showed that increasing levels of O 2 result in progressively greater enhancement of [Ca 2+ ] i and mitochondrial fragmentation, but interestingly, cell proliferation is increased until >60% O 2 levels are reached when cell death is predominant (Hartman et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms in the context of inflammation (Hartman et al, 2012), hypercontractility (Faksh et al, 2016), and fibrosis (Vogel et al, 2017) have been explored to some extent. In this regard, there is increasing recognition that O 2 effects in specific cell types and the types of changes are dependent on extent of exposure structure/function, where with higher levels of O 2 promote bronchopulmonary dysplasia (Wang et al, 2014;Pabelick et al, 2017), but even moderate hyperoxia can contribute to bronchial changes. For example, at a cellular level, we previously showed that increasing levels of O 2 result in progressively greater enhancement of [Ca 2+ ] i and mitochondrial fragmentation, but interestingly, cell proliferation is increased until >60% O 2 levels are reached when cell death is predominant (Hartman et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms responsible for airway dysfunction and thickening in preterm infants that lead to subsequent recurrent wheezing and asthma remain incompletely understood. Although hyperoxia can be expected to induce oxidant stress and thus activate a number of pathways relating to inflammation (13), hypercontractility (9), and fibrosis (8), antioxidants per se have not been shown to be effective (34). Furthermore, the extent of hyperoxia exposure (O 2 concentration and/or duration) clearly colors the picture of which cell types are affected and what structure/function changes occur, with the understanding that high levels of O 2 promote bronchopulmonary dysplasia (14,34).…”
Section: Discussionmentioning
confidence: 99%
“…Despite close monitoring, mounting evidence from various clinical and experimental observations suggests that neonatal hyperoxia causes systemic injury to several organs. Hyperoxia is a key contributor to neonatal and pediatric lung diseases, including airway disease (wheezing and asthma) and bronchopulmonary dysplasia [6]. Chronic exposure to hyperoxia causes oxidative stress and contributes to the pathogenesis of injury in the preterm as well as full-term brain, with a dramatic deterioration of brain function in later life [7].…”
Section: Introductionmentioning
confidence: 99%